MEMAHAMI PERILAKU INDIVIDU DALAM TEORI MANAJEMEN: KUNCI MENUJU ORGANISASI YANG EFEKTIF - Maudinah, Nur Hikmah; Mahfud; Suban, Alwan (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
Individual behavior within organizations is a crucial aspect of management theory that contributes to workplace effectiveness. This study aims to understand the factors influencing individual behavior, including internal aspects such as personality, motivation, perception, and emotions, as well as external aspects such as the work environment and organizational culture. Using a literature review method, this research analyzes personality theories, motivation theories, and behavioral approaches in management. The findings indicate that understanding individual behavior can help organizations enhance productivity, efficiency, and job satisfaction through effective human resource management strategies. Furthermore, management theory plays a vital role in fostering a positive work environment, formulating effective policies, and motivating employees to achieve organizational goals. The implications of this study provide insights for managers in developing behavior-based policies and open avenues for further research on behavioral dynamics in the workplace.